2020
DOI: 10.14309/ctg.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Individuals at Increased Risk for Pancreatic Cancer in a Community-Based Cohort of Patients With Suspected Chronic Pancreatitis

Abstract: OBJECTIVES: We lack reliable methods for identifying patients with chronic pancreatitis (CP) at increased risk for pancreatic cancer. We aimed to identify radiographic parameters associated with pancreatic cancer in this population. METHODS: We conducted a retrospective cohort study of patients with suspected CP within an integrated healthcare system in Southern California in 2006–2015. Patients were identified by a diagnostic code and confirmed by imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
11
0
2
Order By: Relevance
“…The domains of the Newcastle-Ottawa Scale are listed for each study in Table 2 (21–45). The risk of bias in the included studies was low to moderate because of limitations in demonstration of outcome at the start of the study and adequate length of follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The domains of the Newcastle-Ottawa Scale are listed for each study in Table 2 (21–45). The risk of bias in the included studies was low to moderate because of limitations in demonstration of outcome at the start of the study and adequate length of follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported the CIRs of PDAC over time after the diagnosis of CP ( 21 , 22 , 24 , 25 , 29 , 30 ). Data were insufficient to conduct meta-regression because of the small number of studies, and data for covariates of interest were not consistently available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, several studies show that the probability PDAC development can be further increased by including additional factors such as weight change, ethnicity, and lifestyle factors that are commonly contained in electronic medical records. [171][172][173][174][175][176][177][178] Other well-known high-risk populations must be considered in identifying patients who need screening with imaging and liquid biopsy approaches. For example, chronic pancreatitis especially those who develop diabetes with chronic pancreatitis have the highest proportional risk of developing PDAC.…”
Section: Identifying High-risk Populations For Screening and Monitoringmentioning
confidence: 99%
“…Additionally, alcohol consumption and smoking, both well-known risk factors for PDAC, form important confounding factors as patients with CP often have a history of alcohol- and nicotine abuse[ 26 ]. Other risk factors are older age at disease onset, obesity, concurrent DM and pancreatic duct dilatation[ 27 , 28 ].…”
Section: Cp and Pancreatic Cancermentioning
confidence: 99%